Mongolia : Background Paper. (IMF Staff Country Reports; Country Report ;, 1995)
This Background Paper analyzes the social expenditures in Mongolia during the 1990s. The paper highlights that the share of social protection expenditure in total expenditure of the general government has been dropping since 1990, mainly as a result of reduced subsidies after price liberalization on consumer goods. The paper discusses that the share of pensions, education, and health expenditures remained approximately the same through 1993, but in real terms decreased considerably. The paper also examines the key features of the taxation system of Mongolia.